FUNGSI KONSUMSI RUMAH TANGGA DI INDONESIA (PENDEKATAN MODEL KOREKSI KESALAHAN) - Maryam Sangaji (Journal of Indonesian Applied Economics, 2009)
Keynesian theory about consumption states that household consumption (C) relatedpositively with present income:  the greater  income  the more consumption. Besidethat,  interest rate  influence negatively  toward household consumption, because  ifthe interest rate is low then the loan cost  also low, so the factor encourage householdto increase it consumption. The results showed that income level related positivelywith  household consumption level. While the interest rate related negatively  withconsumption  level.  It means  that  the  greater  income encourage  the household  toincrease its consumption. But the increase is not as high as the income level. Thenthe higher interest rate will cause the household increase its saving, so decrease theconsumption. The test by using error correction model (ECM) showed that balancevariable of ECT is significant, where for that the household consumption adaptedwith the income level change and the interest rate at the same period.Keywords: Household  Consumption  Level,  Income,  Interest  Rate,  and  ErrorCorrection Model.